Enhanced Decolourization of Solar Orange RSN by White-rot Fungus Ganoderma lucidum IBL-05 - Nawaz Bhatti, Haq; Tabassam, Sadia; Asgher, Muhammad (Asian Journal of Chemistry, 2010)
This study deals with the process optimization of biological decolourization of dye solar orange RSN, a synthetic textile by Ganoderma lucidum IBL-05. In initial time course study of 10 d, a maximum decolourization (55 ± 3 %) of solar orange RSN was caused by Ganoderma lucidum IBL- 05 after 7 d. The effect of media composition, initial pH of the solution, incubation temperature, carbon and nitrogen additives and initial dye concentration was investigated. Maximum dye decolourization (92 ± 4 %) was achieved in basal nutrient medium II containing 0.01 % solar orange RSN and supplemented with 1 % glucose and maize seed meal after 3 d incuba-tion at pH 4.5 and 30 ºC. The ligninolytic profile of G. lucidum IBL-05 was also investigated and manganese peroxidase was the dominant enzyme activity involved in biodegradation of solar orange RSN with minor activities of lignin peroxidase and laccase.